Extrusion the definitive processing guide and handbook - Wagner, John R., Jr (William Andrew, 2014)
The second edition of Extrusion is designed to aid operators, engineers, and managers in extrusion processing in quickly answering practical day-to-day questions. The first part of the book provides the fundamental principles, for operators and engineers, of polymeric materials extrusion processing in single and twin screw extruders. The next section covers advanced topics including troubleshooting, auxiliary equipment, and coextrusion for operators, engineers, and managers. The final part provides applications case studies in key areas for engineers such as compounding, blown film, extrusion blow molding, coating, foam, and reprocessing. This practical guide to extrusion brings together both equipment and materials processing aspects. It covers basic and advanced topics, for reference and training, in thermoplastics processing in the extruder. Detailed reference data are provided on such important operating conditions as temperatures, start-up procedures, shear rates, pressure drops, and safety. A practical guide to the selection, design and optimization of extrusion processes and equipmentDesigned to improve production efficiency and product qualityFocuses on practical fault analysis and troubleshooting techniques.
Includes index.
Keywords: plasty; vytlačování plastů; extrudéry; plastics; plastic extrusion; extruders; příručky; elektronické knihy; handbooks, manuals, etc; electronic books